2021
DOI: 10.1111/aos.14959
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive model for measuring real‐life cost‐effectiveness in eyecare: automation in care and evaluation of system (aces‐rwm™)

Abstract: This paper describes a holistic, yet simple and comprehensible, ecosystem model to deal with multiple and complex challenges in eyecare. It aims at producing the best possible wellbeing and eyesight with the available resources. When targeting to improve the real‐world cost‐effectiveness, what gets done in everyday practice needs be measured routinely, efficiently and unselectively. Collection of all real‐world data of all patients will enable evaluation and comparison of eyecare systems and departments betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…12 It is widely acknowledged how different conclusions continue to be drawn from same and expanding evidence, depending on different cultures and decision-making policies. 13 This applies not only to ISBCS but also to the selection of antibiotics for prophylaxis of endophthalmitis. The 2017 Cochrane review found five studies meeting the inclusion criteria for reviewing perioperative antibiotics for prevention of acute endophthalmitis after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 It is widely acknowledged how different conclusions continue to be drawn from same and expanding evidence, depending on different cultures and decision-making policies. 13 This applies not only to ISBCS but also to the selection of antibiotics for prophylaxis of endophthalmitis. The 2017 Cochrane review found five studies meeting the inclusion criteria for reviewing perioperative antibiotics for prevention of acute endophthalmitis after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As current information technologies allow automated recording of the important parameters and clinical measures, all real-world data need to become available for national and international benchmarking purposes in search for optimal level of care within an affordable healthcare system. 13…”
Section: Discussionmentioning
confidence: 99%
“…This study is a sub-analysis of real-world data (RWD) collected for the 'Big 4' eye diseases which are AMD, glaucoma, diabetic retinopathy and cataract, containing overall 195 300 interventions in 2008-2020 in Tays Eye Centre, Tampere University Hospital, Finland (Tuulonen et al, 2021). For this single-center retrospective analysis, we included RWD collected manually from electronic medical records of all patients with 1) an ICD-10 code for nAMD (H35.31) and ≥1 CKD05-code for an intravitreal injection, and 2) patients with an ICD-10 code for glaucoma (H40.1, H40.2, H40.3, H40.4, H40.5, H40.6, H40.8, H40.9) and ≥1 visit in Tays Eye Centre, between 1 January 2008 and 31 December 2017.…”
Section: At Er I a L S A N D M Et Hod Smentioning
confidence: 99%
“…Age-related macular degeneration and glaucoma are the most common causes for permanent visual impairment in developed countries, including Finland (Resnikoff et al, 2004;Tuulonen et al, 2021). Glaucoma may be more common among patients with neovascular agerelated macular degeneration (nAMD) than without nAMD (Hu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients in everyday practices have two eyes with variable comorbidities and may be cared by practitioners with unwarranted variations in the delivery of eye care (MacEven et al, 2019).When targeting to improve the real-world costeffectiveness, what is done clinically in everyday practices needs to be measured and evaluated routinely, efficiently and non-selectively (WHO, 2023). Therefore, the Finnish University Eye Clinics have developed a holistic, yet simple and comprehensible aces-rwm™ ecosystem model (automation in care and evaluation of system with real-world monitoring) to deal with complex challenges in everyday eye care (Tuulonen et al, 2022). The overall aim of the ecosystem is to produce the best possible well-being and eyesight with the available resources.…”
mentioning
confidence: 99%